2019
DOI: 10.1039/c9se00123a
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of toxicity reduction in ZnS substituted CdS:P3HT bulk heterojunction solar cells fabricated using a single-source precursor deposition

Abstract: An investigation into how replacing CdS with ZnS reduces toxicity and alters the power conversion efficiency in photovoltaic devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…In another instance, the volume of materials used for Silicon (Si) solar cell fabrication (~200 µm and above [1]) and the sawed wafer from ingots present huge material waste [2]. Its degradation at the termination of the device lifespan reportedly causes about 1 kg of silicon to release approximately 1.58 kg of CO2 into the atmosphere [3]. The alternative materials used in thin-film technologies also pose some possible threats [4], coupled with the challenge of limited resources as they are not as abundant as Si.…”
Section: Introductionmentioning
confidence: 99%
“…In another instance, the volume of materials used for Silicon (Si) solar cell fabrication (~200 µm and above [1]) and the sawed wafer from ingots present huge material waste [2]. Its degradation at the termination of the device lifespan reportedly causes about 1 kg of silicon to release approximately 1.58 kg of CO2 into the atmosphere [3]. The alternative materials used in thin-film technologies also pose some possible threats [4], coupled with the challenge of limited resources as they are not as abundant as Si.…”
Section: Introductionmentioning
confidence: 99%
“…P3HT was selected as it is a well research and utilised electron-donating component of many solar cells (3,4). ZnS was selected due to its low associated toxicity, an important factor often overlooked when selecting photovoltaic materials (5,6). To simplify the fabrication of these photovoltaic materials, a single-step deposition method was used with a single-source precursor (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…ZnS was selected due to its low associated toxicity, an important factor often overlooked when selecting photovoltaic materials (5,6). To simplify the fabrication of these photovoltaic materials, a single-step deposition method was used with a single-source precursor (6)(7)(8). A zinc ethyl xanthate (ZnXan) precursor was selected due to the low temperatures required for decomposition to ZnS, causing little damage to the polymeric component, allowing for a single step deposition of a hybrid bulk heterojunction photovoltaic devices (6,(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…need for an additional sulfur source. 23 Therefore, it is highly beneficial to select an appropriate precursor for 24 the single-step deposition of CZTS active layers, while also utilising a highly 25 scalable process. Furthermore, the selected precursor should preferably func- 26 tion as a low temperature precursor, as it has been well reported that high 27 temperatures can result in the loss volatile components (such as SnS and S) 28 damaging the stoichiometry of the CZTS active layer [18,20,[22][23][24].…”
mentioning
confidence: 99%
“…Furthermore, the selected precursor should preferably func- 26 tion as a low temperature precursor, as it has been well reported that high 27 temperatures can result in the loss volatile components (such as SnS and S) 28 damaging the stoichiometry of the CZTS active layer [18,20,[22][23][24]. 29 Metal xanthates have been used as a low temperature single-source pre- 30 cursor to form metal sulfides, with the general formula [M(S 2 COR) n ], where 31 R is an alkyl group, and have been shown to be viable precursors for Cu 2 ZnSnS 4 32 [21, [25][26][27][28][29]. It has been suggested that metal xanthates decompose via the 33 Chugaev elimination reaction [30], as shown in Figure 1.…”
mentioning
confidence: 99%